(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
To predict textile quality fluctuation from the perspective of uncertainty factors, first, the reasons and patterns of quality fluctuation in the industrial textile processing were analyzed, and knowledge representation of textile quality attributes was studied. Second, through the theories of human-machineenvironment- system-engineering (HMESE), probability, and statistics, the uncertainty factors that affect textile production quality were extracted, and generation mechanism, interaction relationship and behavioral characteristics of them was explored. Then, an improved human-machine-environment brittle model oriented to the textile processing was built. As verified by the experiment and simulation, the results have shown that the improved brittle model has achieved a full range analysis of quality uncertainty of the textile, which are from the reason and pattern of quality fluctuation to generation mechanism, mutual relations, and behavior identification of the uncertainty factors.